Stability and variability of rower`s motions (Rowing Biomechanics Newsletter, 2012)
Rowing is a cyclic sport that means it requires repeating a similar cycle of motions many times. Usually, 200-250 stroke cycles are performed to cover the standard racing distance of 2000m. Visually, all strokes look the same and only good experts could see some small differences. Biomechanical equipment allowsn very accurate measurements of rowing motions and software allows determining how consistent or variable motions of each rower in a crew are. This article describes these stability and variability of rower`s motions. Mention: 1. Catch is more difficult for coordination of rower`s motions than finish. 2. Crew rowers have higher complexity of their motions, because they have to coordinate them with the stroke rower.